PENGARUH KRISIS MONETER PADA EFISIENSI PERUSAHAAN PUBLIK DIBURSA EFEK JAKARTA - Mas'ud Machfoedz (Faculty of Economics and Business, Universitas Gadjah Mada, 1999)
The monetery crisis has attacted Indonesia since the mid of 1997. Sharp increase ofUS dollar exchange rate and the due of international loan hurted Indonesianeconomy and business painfully. It is very rational that this national probleminfluence the performance of companies listed in Jakarta Stock Exchange (JSX).Increasing the price, in rupiah, of imported material and other goods and servicesfrom other countries that based on dollar value destortedthe ability of companies tomaintain their financial performance.This study intent to identify and analyze the impact of monetary crisis to theperformance of companies listed in JSX. 129 manufacturing companies selected assample to answer the question whether the monetary crisis has already attacted theperformance of companies listed in JSX. The sample, then, sub-grouped to the foursub-sample based on sector of businesses to explain which of the sector hurting most.By using t-test and spearman rank correlation all the hypothesis are tested. Sixfinancial ratios used to represent the company performance. Those ratios are consistof three ratio categories: profitability, liquidity and operation, and leverage.The results of the study shown that companies listed in JSX are impacted by monetarycrisis. All means of financial ratios after crisis used in this study are worse than thosein the year before crisis. T-test results show that all indicators of ratios significantlydifferent except Current Ratio and Debt to Equity Ratio. The explanation that can beprovided from these findings is that the impact of crisis to those two ratios cannot beshown in the very short time (only six months), because the liquidity, debt, and equityof the sample are still not significantly changing from the first semester of the year of1997. The explanation of those finding also supported by analysis of sectors ofindustry. Four sectors, taken from JSX directory, shown consistently with totalsample except sector of heavy investment as: building construction, real estate, and other heavy investment industries. The explanation of this exception is that thosecompanies in sector 4 have not yet been impacted by the crisis.